PENGARUH PILATES EXERCISE TERHADAP NYERI HAID PADA REMAJA PUTRI - Doloksaribu, Meli Doloksaribu (Nursing Arts, 2023)
Menstruation is the release of the lining of the uterus (endometrium) which is accompanied by bleeding and leaves only the basal layer. This menstrual process takes place regularly every month for every woman. There are many problems that arise during menstruation such as menstrual irregularities, menorrhagia, dysmenorrhea, and other related symptoms. Among these complaints, dysmenorrhea is the most frequently reported problem, dysmenorrhea occurs in 60% -90% of adolescents, and is the cause of reduction in daily activities. This study aims to determine the effect of pilates exercise on reducing menstrual pain in young women. Method used Pre-experiment with the one group pre-test and post-test design approach to determine the effect of Pilates Exercise on reducing menstrual pain in adolescents who experience menstrual pain. The results of the Wilcoxon test obtained a p-value of 0.000 (p